2016
DOI: 10.1074/jbc.m116.714824
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of RANTES and Eotaxin Prevents the Loss of Dopaminergic Neurons in a Mouse Model of Parkinson Disease

Abstract: Parkinson disease (PD) is second only to Alzheimer disease as the most common human neurodegenerative disorder. Despite intense investigation, no interdictive therapy is available for PD. Recent studies indicate that both innate and adaptive immune processes are active in PD. Accordingly, we found a rapid increase in RANTES (regulated on activation normal T cell expressed and secreted) and eotaxin, chemokines that are involved in T cell trafficking, in vivo in the substantia nigra pars compacta and the serum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…Recently we have demonstrated that RANTES and eotaxin are rapidly induced in serum and nigra of MPTP-intoxicated mice and that neutralization of these two chemokines by functional blocking antibodies protects the nigrostriatum from MPTP toxicity (7). Here, to understand any possible relationship between spontaneous reversal of disease and RANTES/eotaxin, we examined the mRNA and protein levels of these chemokines in MPTP mouse model after 1d, 3d, 7d, 30d, and 60d of MPTP insult.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently we have demonstrated that RANTES and eotaxin are rapidly induced in serum and nigra of MPTP-intoxicated mice and that neutralization of these two chemokines by functional blocking antibodies protects the nigrostriatum from MPTP toxicity (7). Here, to understand any possible relationship between spontaneous reversal of disease and RANTES/eotaxin, we examined the mRNA and protein levels of these chemokines in MPTP mouse model after 1d, 3d, 7d, 30d, and 60d of MPTP insult.…”
Section: Resultsmentioning
confidence: 99%
“…Although we observed some increase in different proinflammatory cytokines in the serum of hemiparkinsonian monkeys after 37 d of MPTP intoxication, marked increase was found for chemokines like RANTES and eotaxin in the serum of hemiparkinsonian monkeys as compared to control serum (6). Recently, we have demonstrated that RANTES and eotaxin are upregulated in MPTP-intoxicated mice as well as postmortem PD brains as compared to age-matched controls and that functional blocking antibodies against RANTES and eotaxin protects against nigrostriatal degeneration in MPTP-intoxicated mice (7), indicating the involvement of these two chemokines in parkinsonism. Microglia in the nigra of hemiparkinsonian monkeys, MPTP-intoxicated mice and postmortem PD brains express RANTES and eotaxin (6, 7), suggesting that microglia-derived RANTES and eotaxin is the source of these chemokines in the serum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microglial clustering around neuritic plaques contribute the neuroinflammation, and progressive neurodegeneration and CCL5 down-regulation reduce chemotaxis of microglia toward Aβγaggregates (Huang et al, 2010). Furthermore, it has also been demonstrated that CCL5 is up-regulated in the substantia nigra of PD mouse models and the neutralization of CCL5 protects against nigrostriatal degeneration (Chandra et al, 2016). CXCL3 has also been found to be upregulated other disease states (Martín-Fuentes et al, 2009; See et al, 2014; Gui et al, 2016).…”
Section: Discussionmentioning
confidence: 99%